2014
DOI: 10.1186/s12913-014-0564-7
|View full text |Cite
|
Sign up to set email alerts
|

Training needs and supports for evidence-based decision making among the public health workforce in the United States

Abstract: BackgroundPreparing the public health workforce to practice evidence-based decision making (EBDM) is necessary to effectively impact health outcomes. Few studies report on training needs in EBDM at the national level in the United States. We report competency gaps to practice EBDM based on four U.S. national surveys we conducted with the state and local public health workforce between 2008 and 2013.MethodsWe compared self-reported data from four U.S. national online surveys on EBDM conducted between 2008 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 42 publications
3
53
2
1
Order By: Relevance
“…A summary of four US surveys of state and local public health practitioners identified three skills where the gaps in capacity are largest between importance and availability: economic evaluation, communicating research to policymakers, and adapting interventions from one setting or population to another (103). The shortage of economic data has also been observed in England (115).…”
Section: Challenges and Opportunities For Research And Practicementioning
confidence: 99%
“…A summary of four US surveys of state and local public health practitioners identified three skills where the gaps in capacity are largest between importance and availability: economic evaluation, communicating research to policymakers, and adapting interventions from one setting or population to another (103). The shortage of economic data has also been observed in England (115).…”
Section: Challenges and Opportunities For Research And Practicementioning
confidence: 99%
“…Finally, there were several interrelated reasons for surveying representatives from the Departments of Education and Public Health, in addition to Extension. Although a national survey assessing training needs of the public health workforce concerning evidenced-based decision making recently has been conducted (Jacob et al 2014), other relevant types of readiness assessments were not found. Most importantly, the design for the PROSPER Partnership Model entails active collaboration of Extension systems with DOEs and DPHs, as potential supporters of EBP delivery.…”
Section: Gaps In the Literature And Related Research Questionsmentioning
confidence: 99%
“…Training in EBDM can improve skills needed to use EBDM processes (5). EBDM is also recognized as having an impact on the effectiveness of chronic disease units (6).…”
Section: Introductionmentioning
confidence: 99%